Dispute Resolution Policy On Leasing Agreements In The Context Of Legal Protection Against Customers - Syaiful Asmi Hasibuan; M. Hary Angga Pratama Sinaga; Robiatul Adawiyah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Even if the execution of objects that are the object of fiduciary guarantees can be done by the implementation of fiduciary excutorial. However, the execution carried out by using the services of debt collectors is an act that is beyond the limits of humanity and violates the ethics of the law itself. In addition to the customer is also not good and is a weakness in the status of motor vehicles that experience wansprestasi. So this is the background of the author to raise and become the topic of discussion in writing the thesis with the title of the settlement policy of the case in the leasing agreement in the framework of legal protection of customers. The type of research used is normative legal research that is descriptive analysis, by outlining the data in the form of sentences arranged in a systematic, clear and detailed which is then interpreted to obtain a conclusion will be put forward in the form of a systematic description. As a result of the default of the lessee, the lessor has the right to take back the lease object that is in the power of the lessee. If the collection of these items is not inhibited by the lessee, then there is no problem that will arise. However, problems will arise if the lessee without the right to prevent or inhibit the return of the lessor's property. In this case there are several ways that can be used in resolving disputes arising from both parties, namely : 1) peaceful, 2). District Court. 3) Alternative Dispute Resolution (ADR), there are many alternatives in dispute resolution: a. Arbitration, b. Negotiations, c. Mediation, d. Conciliation, e. The judge, f. Fact-finding.